R-continuous functions - Ch. Konstadilaki-Savvapoulou; D. Janković (International Journal of Mathematics and Mathematical Sciences)
A strong form of continuity of functions between topological spaces is introduced and studied. It is shown that in many known results, especially closed graph theorems, functions under consideration are R-continuous. Several results in the literature concerning strong continuity properties are generalized and/or improved.